Theoretical investigation of catalytic n-butane isomerization over H-SSZ-13 - Spiske, Lucas; Plessow, Philipp N.; Kazmierczak, Kamila; Vandegehuchte, Bart D.; Studt, Felix (Frontiers in Catalysis, 2023)
Hybrid density functional theory calculations are used to investigate different mechanisms of the isomeri-zation of n-butane to isobutane. The monomolecular mechanism is found to be prevalent, with a Gibbs free energy barrier of 155 kJ/mol at 400 °C, compared to the bimolecular mechanism (190 kJ/mol) due to less favorable entropy for the latter. Hydrogen transfer reactions that convert olefins into alkanes (and vice ver-sa) are also included in the investigations, and show an energy barrier of 203 kJ/mol for the conversion of isobutene to isobutane. Additionally, a methyl-transfer mechanism is discussed as a possible pathway for formation of C3 and C5 side products, in competition to the bimolecular mechanism; the highest barrier of the initial methyl transfer is calculated to be 227 kJ/mol. We discuss the influence of entropy and anhar-monicity on all mechanisms, stating that through the uncertainties in computational methods when calculat-ing these systems, they are very likely to be strongly overestimated here. Therefore, all mechanisms stud-ied here can still be feasible within the reaction network.